Performance Evaluation of a Fully Automated Molecular Diagnostic System for Multiplex Detection of SARS-CoV-2, Influenza A/B Viruses, and Respiratory Syncytial Virus - James G. Komu; Dulamjav Jamsransuren; Sachiko Matsuda; Haruko Ogawa; Yohei Takeda (Diagnostics)
Background/Objectives: Concurrent outbreaks of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A and B viruses (IAV/IBV), and respiratory syncytial virus (RSV) necessitate rapid and precise differential laboratory diagnostic methods. This study aimed to evaluate the multiplex molecular diagnostic performance of the geneLEAD VIII system (Precision System Science Co., Ltd., Matsudo, Japan), a fully automated sample-to-result precision instrument, in conjunction with the VIASURE SARS-CoV-2, Flu & RSV Real Time PCR Detection Kit (CerTest Biotec, S.L., Zaragoza, Spain). Methods: The specific detection capabilities of SARS-CoV-2, IAV/IBV, and RSV genes were evaluated using virus-spiked saliva and nasal swab samples. Using saliva samples, the viral titer detection limits of geneLEAD/VIASURE and manual referent singleplex RT-qPCR assays were compared. The performance of geneLEAD/VIASURE in analyzing single- and multiple-infection models was scrutinized. The concordance between the geneLEAD/VIASURE and the manual assays was assessed. Results: The geneLEAD/VIASURE successfully detected all the virus genes in the saliva and nasal swab samples despite some differences in the Ct values. The viral titer detection limits in the saliva samples for SARS-CoV-2, IAV, IBV, and RSV using geneLEAD/VIASURE were 100, ≤10−2, 100, and 102 TCID50/mL, respectively, compared to ≤10−1, ≤100, ≤100, and ≤104 TCID50/mL, respectively, in the manual assays. geneLEAD/VIASURE yielded similar Ct values in the single- and multiple-infection models, with some exceptions noted in the triple-infection models when low titers of RSV were spiked with high titers of the other viruses. The concordance between geneLEAD/VIASURE and the manual assays was high, with Pearson’s R2 values of 0.90, 0.85, 0.92, and 0.95 for SARS-CoV-2, IAV, IBV, and RSV, respectively. Conclusions: geneLEAD/VIASURE is a reliable diagnostic tool for detecting SARS-CoV-2, IAV/IBV, and RSV in single- and multiple-infection scenarios.